Forming new words: compounding in children with developmental language disorders - Giesselbach, Lisa; Scherger, Anna-Lena (Frontiers in Language Sciences, 2025)
Compounding is a common word-formation strategy in Germanic languages such as English and German. This study focuses on German compounding, which is highly productive and frequently used to create new words. The ability to form new words through compounding has been observed in German-speaking children from the early stages of language acquisition. There is evidence suggesting that children with Developmental Language Disorder (DLD) may struggle with understanding and producing compounds compared to their peers with typical development (TD). These difficulties include challenges with the correct order of compound components. The present study examined compounding competence, specifically focusing on the correct ordering of compound components, in children with DLD and TD aged 4 to 5 years. Two elicitation tasks were conducted. In experiment 1, we compared the word-formations of 28 children with TD and 28 children with DLD when naming low-frequency everyday objects with those of an adult control group (n = 10) from a pilot-study. Across all three groups, compounds were the predominant word-formation strategy, with no difference between the three groups. Experiment 2 involved a production and a reception task using novel compound nouns. It was applied to 31 children with TD and 30 children with DLD. Furthermore, we compared the results of the production task with an adult control group from a pilot-study (n = 23). Both child groups produced compounds with word-order errors (inversions). In the production task, inversion rates did not differ significantly between the two child groups, but both inverted compound components significantly more often than the adult control group. However, in contrast to expectations, children with TD showed more inversions than children with DLD in the reception task (U = 296.5, Z = −2.4, p = 0.014). Taking into account methodological issues, we concluded that compounding might serve as a linguistic resource for children with DLD, as they may rely on it to fill lexical gaps, especially when receiving and comprehending language. Further research is needed to deepen our understanding of processing and acquisition of compounds in children with DLD and TD, taking into account the high inversion rates of the children aged 4 to 5 years.